Estrategias de aprovechamiento de residuos sólidos producidos por las celdas fotovoltaicas en el aprovechamiento de la energía solar en proyectos de producción más limpia en Colombia (2021)
Photovoltaic solar energy is a type of renewable energy which uses the use of solar rays, by storing this energy by cells or solar modules, especially silica type. This document presents an analysis of photovoltaic solar energy in order to define the appropriate strategies for the use of waste from photovoltaic solar panels at the end of their useful life, for which the generalities and main characteristics will be analyzed in this paper. of the different components and materials that the photovoltaic solar panels present. In addition, the application of the three (3) r's as a cleaner production principle and its application in the use of solar panels at the end of their useful life and the creation of a value market for raw materials is described. Based on the foregoing, case studies of the use of leading countries in photovoltaic systems are presented, such as Germany, the United Kingdom, the United States, Japan, China and India, based on the WEEE policy (Waste Electrical and Electronic Equipment). ) and waste management policies of those countries, and their influence as an example in future energy projects of a photovoltaic nature in Colombia.